The Effectiveness of RME Based Learning on Junior High School Students' Mathematical Procedural Fluency and Mathematical Disposition - Fathina, Naila; Azizah, Dewi; Sarian, Hazen Mellai Xyza B (Circle: Jurnal Pendidikan Matematika, 2025)
This study aimed to examine the differences in mathematical procedural fluency and mathematical disposition between students who received instruction using the RME approach and those taught using the expository approach. The type of research employed was a quasi-experimental study with a posttest-only control group design. The subjects consisted of two seventh-grade classes at SMP Negeri 13 Pekalongan. The instruments used included an essay test and a Likert-scale questionnaire. Data analysis was carried out using the R software. The assumption tests applied were the Shapiro–Wilk test for univariate normality, the Henze–Zirkler test for multivariate normality, the F-test for univariate homogeneity, and Box’s M test for multivariate homogeneity. Hypothesis testing was conducted using Hotelling’s T² test for multivariate analysis. The result showed a p-value of 8.02e-06 < 0.05, indicating a significant difference between the two groups. Follow-up analysis using the Mann–Whitney U test revealed a significant difference in procedural fluency (p = 3.21e-05), while the independent t-test showed no significant difference in mathematical disposition (p = 0.3207). The mean score for procedural fluency in the RME class was higher than that of the expository class. These findings suggest that the RME approach is more effective in improving students’ procedural fluency, although it has not yet shown a significant effect on mathematical disposition.